Review Artikel: Resistensi HIV dan Mekanisme Kerja Antiretroviral - Siti Fatimah Azzahra; Muhammad Farid Maksum (Jurnal Biodiversitas dan Bioteknologi, 2025)
HIV (Human Immunodeficiency Virus) is a virus that attacks the human immune system, especially CD4 cells which are important for the body's defense against infection. Untreated HIV infection can lead to AIDS (Acquired Immunodeficiency Syndrome), a condition in which the immune system is very weak and susceptible to various opportunistic infections and cancers. HIV has become one of the most challenging global health problems, with millions of people infected and dying each year. One of the greatest advances in HIV treatment is the development of antiretroviral therapy (ARV). This therapy uses a combination of several drugs to suppress viral replication in the body, slow the progression of the disease, and prolong the patient's life expectancy. However, the long-term success of this therapy is threatened by the emergence of resistance to antiretroviral drugs. The mechanism of action of ARVs involves several steps in the HIV life cycle, including protease inhibitors, reverse transcriptase inhibitors, and integrase inhibitors. This study uses a literature review method and involves 15 relevant journals to discuss HIV resistance and the mechanism of action of ARVs. The results of the study showed that ARV therapy is effective in improving the health of HIV patients, but the effectiveness and retention of therapy are greatly influenced by the time of therapy initiation, type of therapy, and disclosure of the patient's HIV status.